Developing an Interview Guide for Online Focus Group Discussions during the Crisis of the COVID-19 Pandemic - Joungtrakul, Jamnean; Chaiyasoonthorn, Wornchanok; Chitwattanakorn, Trakul; Rojsurakitti, Terdsak; Klinpong, Samita; Rikharom, Rujira (My University, 2025)
Introduction: Focus group discussion is one of the most widely recognized methods of data collection in qualitative research. This approach allows participants to engage and motivate their concepts, providing insight that is not easily obtained from individual interviews. It is a valuable means of gaining insight from subjects through participatory experience. Researchers collect various types of realistic information by way of interactions, exchanges, and feedback that is shared. In addition, focus groups help researchers understand the personal perspectives of their participants by observing their interactions, creative responses, and flexibility within the interview or dialogue. They also help researchers to collect a large amount of data in a short time. Currently, focus group discussion (FGD) has developed and progressed from the traditional focus group (TFG) into an online focus group (OFG). Several options are available for OFG, such as Zoom, or other cloud meeting platforms. Such platforms offer flexibility and help reduce costs. This was particularly evident during the COVID-19 pandemic. Preventive measures that were imposed, such as travel restrictions, social distancing, and limits on gatherings, created limitations on data collection for researchers trying to complete their research projects. Initial reviews, however, indicate that studies in Thai language of OFG methods remain limited, especially regarding the development of tailored interview guides. Content: The essence of this article presents the process of developing an interview guide for OFGs. It begins with an introduction to the study's key topics, starting with the concept of focus group discussions as a foundation for understanding their traditional meaning and components, known as in-person focus group interviews. It then explores the transition to online focus groups, which evolved from traditional discussions using digital technology as a communication tool. The next section outlines the steps for conducting online focus groups to foster relationships, enhance engagement, and encourage participants to share opinions, exchange knowledge, and experiences. The article further discusses the development of an interview guide specifically for online focus groups, highlighting key components such as adaptable question topics that can be adjusted in number as needed. Finally, it details the process of constructing the interview guide, adapting the in-depth interview framework based on variations in the number of questions, while incorporating visuals and tables that effectively connect to the content in a comprehensive manner. Conclusion: Traditional focus groups meet in physical locations for data collection, whereas OFGs require technology to operate via online networks instead. Important steps for running OFGs include cautious planning, the selection of appropriate technology and testing it before use, adjusting content, organizing schedules, assigning roles, and protecting personal data. Recorded visuals and conversation data should be finally reported to participants. For the process of developing interview guidelines for online focus group discussions in qualitative research, it is essential to emphasize key steps: considering questions and objectives, reviewing literature, drafting questions, selecting and structuring them, ensuring quality, conducting pilot tests, and finalizing the interview guide.
Keywords: Focus Group Discussion; Interview Guide; Online Focus Group; Traditional Focus Group